PARATHYROID GLAND, ANATOM, HISTOLOGY, AND PHYSIOLOGY (A SHORT REVIEW) - Fatimah K. Ibrahim Al- Mahdawi; Abed Sultan Hassan; Wasan A.Wahab i Alsiad (Basrah Journal of Veterinary Research)
Parathyroid glands take a special place in human physiology and anatomy,as they were the last major organs to be identified in humans. The average parathyroid glandmeasures about five to seven mm in length, andthree to four mm in width and weighs about forty to sixty mg. The four parathyroid glands arederivative from the posterior endoderm of the 3rd and 4th pharyngeal pouches. Normally, thereare four parathyroid glands (superior and inferior). It takes the bean-shaped or oval. The mainfunction of the parathyroid gland is to release hormone called parathyroid hormone (PTH)consists of 84- amino acid, which is involved in calcium homeostasis.